Eating behavior of adolescent girls in countries with a high prevalence of stunting under five: a systematic review - Setiawan, Arlette Suzy; Budiarto, Arief; Indriyanti, Ratna (Frontiers in Psychology, 2023)
Background: Adolescence is critical for physical and psychological growth, making healthy dietary behavior essential. Several countries face nutritional challenges due to a high prevalence of stunting in children under five, which can impact adolescent girls' eating behavior. This systematic review aims to provide evidence on the eating behavior of adolescent girls in such countries, offering insights for stunting prevention programs. Methods: We conducted a systematic review following PRISMA guidelines and registered it in PROSPERO. We employed a comprehensive search strategy across multiple databases. Study selection involved three stages: deduplication, title/abstract screening, and full-text review, with inter-reviewer agreement assessment. Results: The search identified 15 eligible studies from various countries, primarily utilizing cross-sectional designs. The studies focused on age ranges within adolescence and varied in sample size and assessment tools. The primary objective of these studies was to assess eating behavior, with outcomes related to dietary patterns, eating disorders, body image, and nutritional knowledge. The results revealed diverse eating behaviors among adolescent girls, including restrained eating, dieting for weight loss, craving-induced eating, and unhealthy dietary patterns. Many girls exhibited low dietary diversity, contributing to micronutrient deficiencies. Suggestions: To address these issues effectively, stunting prevention programs and policies should prioritize the following strategies: implementing comprehensive nutritional education programs to enhance adolescents' knowledge of healthy eating habits and dietary diversity, providing resources and support for positive body image development to reduce the pressure for unhealthy dieting, improving access to affordable, nutrient-rich foods in both urban and rural areas, raising awareness about eating disorders and emphasizing early identification and intervention, engaging parents, caregivers, and communities in promoting healthy eating behaviors, and maintaining rigorous research and monitoring to adapt strategies based on evolving trends in adolescent eating behaviors. Conclusion: Adolescent girls in countries with high stunting prevalence exhibit diverse eating behaviors that can impact their nutritional status and overall health. Addressing these behaviors is essential to prevent stunting and its long-term consequences, emphasizing the importance of comprehensive strategies and support for this vulnerable population.